PROMOTING SUSTAINABLE MANUFACTURING IN FURNITURE PRODUCTION THROUGH ADDITIVE MANUFACTURING (Interdisciplinary Studies Journal, 2026)
The furniture industry represents a traditional economic activity with a significant environmental impact, also characterized by a slow pace in the adoption of advanced technologies. Scientific literature indicates that various Industry 4.0 technologies can contribute to greater productive efficiency and mitigation of environmental impact. This study aimed to analyze the possibilities of promoting sustainable manufacturing in furniture production through additive manufacturing. To achieve this objective, a field survey strategy was chosen, employing a qualitative approach, interviewing 12 professionals holding operational management positions in furniture industries, 10 from Brazil and 2 from Sweden. The content of the interviews was subjected to content analysis. The results showed that additive manufacturing has already become a reality in several industrial organizations, with a significant reduction in environmental impact, both in Brazil and Sweden. The greatest contributions of Additive Manufacturing to promoting sustainable manufacturing were observed in the initial stage of the manufacturing process, namely in product conception, design, project, reduction of raw material waste, rework, minimizing internal movements of raw materials and finished products, as well as decreasing electricity consumption.
Keywords: Sustainable manufacturing; Additive Manufacturing; Furniture manufacturing; Brazil; Sweden